ANALISIS SENTIMEN APLIKASI E-GOVERENMENT PADA GOOGLE PLAY MENGGUNKAN ALGORITMA NAÏVE BAYES - Rini Sartina; Elmayati; Nelly Khairani Daulay (JURNAL ILMIAH BETRIK, 2023)
E-gov is one of the innovations created by the government to be able to compete in the digital world. One government agency that has used e-gov is the Ministry of Spatial Planning/National Land Agency (ATR/BPN). in this study the authors used the Naïve Bayes Algorithm as a classification method to determine positive, negative, and also neutral sentiments. The labeling process shows that the touch my land application tends to get a neutral response which can be seen from the comparison of 4000 data, 2265 positive, 1453 negative and 211 neutral data. and the results of sentiment analysis testing using the Naïve Bayes Algorithm produce an accuracy of 81%, 78% precision, and 79% recall.